If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y = 4(y + 10) Reorder the terms: 5y = 4(10 + y) 5y = (10 * 4 + y * 4) 5y = (40 + 4y) Solving 5y = 40 + 4y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4y' to each side of the equation. 5y + -4y = 40 + 4y + -4y Combine like terms: 5y + -4y = 1y 1y = 40 + 4y + -4y Combine like terms: 4y + -4y = 0 1y = 40 + 0 1y = 40 Divide each side by '1'. y = 40 Simplifying y = 40
| 4(1.5y-1.25)+6y=-5 | | 2*3+4= | | -3x^2+2x+7=0 | | y^2-1=4+y | | 3(y+4)=6y+6 | | 7x+10-6x=11 | | -7v-16=-4v+8 | | -6v+11=-3v-4 | | 13.7b-7.5=-2.3b+8.5 | | -(5y+4)-(-4y-6)=2 | | 0.3u+2.3=-1.2u+3.8 | | 8u+20=3u | | 3(x-4)-4(x-3)=x+3 | | 6x-15=63 | | 3x-19=-x-7 | | 2w-7=5w+8 | | 6(3x-2)=3(6x+3) | | -8x^2(9x^3)=0 | | 3+4y-1=7y+9-2y | | 5(2-2y)-3y=11 | | -8x^2(-10x^4)=0 | | 4x+10=4x | | 3v^2+4v+5=0 | | -11.4x=79.8 | | y-3=4(x-10) | | -3(x+4)=3(x-5) | | s^2+2s-6=0 | | -2(7-2y)+3y=14 | | p*p*p*p= | | 3y+18y=63 | | s^2+2s=6 | | 7-16=5x-4x+4 |